Distance mentoring of health researchers: Three case studies across the career-development trajectory. Issue 2 (October 2017) - Xu, Xiaomeng; Schneider, Margaret; DeSorbo-Quinn, Alexandra L; King, Abby C; Allegrante, John P; Nigg, Claudio R
Despite the crucial role of mentoring, little literature exists that addresses distance mentoring among health researchers. This article provides three case studies showcasing protégés at different stages of career development (one in graduate school, one as an early-stage researcher, and one as an established researcher). Each case study provides a brief history of the relationship, examines the benefits and challenges of working together at a distance, and discusses the lessons learned from both the mentor and the protégé over the course of these relationships. A mentoring model, examples of mentoring communications, and potential promising practices are also provided and discussed.